Forms of Life and Subjectivity - Rueda Garrido, Daniel (Open Book Publishers, 2021)
"Forms of Life and Subjectivity: Rethinking Sartre’s Philosophy explores the fundamental question of why we act as we do. Informed by an ontological and phenomenological approach, and building mainly, but not exclusively, on the thought of Sartre, Daniel Rueda Garrido considers the concept of a ""form of life” as a term that bridges the gap between subjective identity and communities.